AKTIVITAS ENZIM PEROKSIDASE PISANG KEPOK DENGAN APLIKASI GLOMUS TIPE 1 - Suswati .; Asmah Indrawaty; Friardi . (Universitas Lampung, 2015)
Ripe banana peroxidase activities with Glomus type 1. Ripe banana is very susceptible to blood disease caused by Blood disease bacterium (BDB) and Fusarium wilt caused by Fusarium oxysporum f.sp. cubense. Arbuscular mycorrhizal fungi (AMF) Glomus tipe 1 increased resistance of ripe banana seedlings to both wilt diseases. The resistance mechanism related with the change of hydrolytic enzyme activities: peroxidase (PO), phenylalanin amonialyase (PAL) and polyphenoloksidase (PPO). The green house and laboratorium experiment were conducted to study the effect of different colonization time 4, 12, 24, 36, 48, 72, 96 h after application (haa) and control (without AMF) with 3 replicates. AMF fresh inoculants source is a mixture of sand planting medium that containing spores, hyphae and corn root colonized AMF. Ripe banana seedlings (60 days old) were inoculated with 50 g fresh AMF inoculants and incubated with the treatment. The results showed that the application of Glomus tipe 1 caused changes in the enzyme activity of peroxidase in the roots and leaves. Root peroxidase enzyme activity slightly increased 5.84% (0.326U) at the beginning of colonization (4 haa) while peroxidase enzyme activity in leaves sharply declined (85.83–87.37%).